RRI Yogyakarta Brand Communication at the 2022 Nusantara Student Festival Event - Siwi Uswatun; Rila Setyaningsih; Mutiara (Indonesian Journal of Business Analytics, 2024)
Current technological developments have provided significant changes to information media, Information and communication media companies need to always innovate to maintain the company's image and remain the people's choice. The research aims to determine RRI Yogyakarta's brand communication at the 2022 Nusantara Student Festival event. This research uses a qualitative descriptive case study approach to explore and explore in depth. The theory used is brand communication strategy theory with brand visualization (logo) indicators. The research results show that the brand communication strategy implemented by RRI Yogyakarta includes a logo that is disseminated through branding media at the FPN 2022 event location and through Instagram social media, then direct marketing carried out door-to-door and radio broadcasts, social media via Instagram platform, promotions carried out include offers of collaboration and the use of influencers, marketing events through organizing the 2022 Nusantara Student Festival event, as well as sponsorship in the form of service support.